A Flexible, Fireproof, Composite Polymer Electrolyte Reinforced by Electrospun Polyimide for Room-Temperature Solid-State Batteries - Boheng Yuan (MDPI AG, 2021)
Solid-state batteries (SSBs) have attracted considerable attention for high-energy-density and high-safety energy storage devices. Many efforts have focused on the thin solid-state-electrolyte (SSE) films with high room-temperature ionic conductivity, flexibility, and mechanical strength. Here, we report a composite polymer electrolyte (CPE) reinforced by electrospun PI nanofiber film, combining with succinonitrile-based solid composite electrolyte. In situ photo-polymerization method is used for the preparation of the CPE. This CPE, with a thickness around 32.5 μm, shows a high ionic conductivity of 2.64 × 10−4 S cm−1 at room temperature. It is also fireproof and mechanically strong, showing great promise for an SSB device with high energy density and high safety.